Public eating, private pain: Children, feasting, and food security in Vanuatu. Issue 3 (1st October 2016) - Wentworth, Chelsea
ABSTRACT: This article describes how the private problem of food insecurity in Vanuatu becomes public when children seek community feasts to cope with inadequate family food resources. Ethnographic data reveal that community members, particularly women who serve food at feasts, are increasingly aware of the rise in hungry children attending feasts. This is the subject of gossip, as public eating becomes a way that children inadvertently reveal private pain and familial struggle. Data illustrate that negotiating the public and private space in which food insecurity is displayed and communicated is a critical lens for understanding how eating behaviors shape cultural identities.